Emerging updates on tracking new landscapes in nanotechnology for the diagnosis and ovarian cancer therapy - Mamatha Ramani, Seethammagari; Josthna, Penchalaneni; Padma, Kanchi Ravi (Journal of Associated Medical Sciences, 2023)
The sixth most common recurrent malignancy worldwide is ovarian cancer in women, and it causes more women to die compared to any other issue impacting the female reproductive system. Ovarian cancer has several histological subgroups differing in clinical traits, risk factors, cell sources, molecular makeups, and treatment possibilities. There is no effective screening procedure, and it is typically discovered at a late stage. Newly found cancer is currently treated with platinum-based chemotherapy and cytoreductive surgery. Due to its recurrence and late diagnosis, ovarian cancer has the highest fatality rates in contrast to all gynecological cancers. The discipline of medical nanotechnology has made great strides in recent years in resolving issues and enhancing the detection and treatment of various illnesses, including cancer. However, most studies and recent reviews on nanotechnology are devoted to how it might be utilized to treat other tumors or disorders. This review’s main objective was the precise diagnosis and treatment of ovarian cancer using nanoscale drug delivery systems. Various nanocarrier systems, such as dendrimers, nanoparticles, liposomes, nanocapsules, and nano micelles, have been discussed. Additionally, we explore how the potency of the combination of immunotherapy and nanotechnology may help to overcome the current therapeutic constraints connected with each application and reveal a novel paradigm in cancer therapy. The unique nanotherapeutic approaches that have demonstrated promising outcomes in preclinical in vivo research are highlighted, along with new nanoformulations actively advancing into clinical trials. Additionally, the possible use of nanomaterials in diagnostic imaging methods and the capacity to use nanotechnology for early ovarian cancer detection are also highlighted.